The impact of damage etching on fracture strength of diamond wire sawn monocrystalline silicon wafers for photovoltaics use. (2nd November 2018) - Sekhar, Halubai; Fukuda, Tetsuo; Kida, Yasuhiro; Tanahashi, Katsuto; Takato, Hidetaka
Abstract: To reduce silicon kerf loss, we have cut silicon bricks into wafers using a thin diamond wire (the diameter of core wire: 80 µm, the average size of abrasives: 10 µm). Damages caused by diamond wire sawing are responsible to have an asymmetry in fracture strength, a lower strength in parallel bending and a higher strength in perpendicular bending to the saw marks. To elucidate the asymmetry to the depth of subsurface damage, front and backside surfaces of wafers are etched in 3, 5, and 10 µm depth by 24% KOH aqueous solution. By etching 3 and 5 µm, the strength are enhanced by a factor of 1.96 and 2.9 times in parallel bending and by 1.03 and 1.31 times in perpendicular bending compared to bare wafers. Etching more than 5 µm removes the asymmetry, showing the equal strength in the bending in both directions. We cystallographically consider several fracture mechanisms of bare and etched wafers through the observation of each fracture surface.